F94. EFFECTS OF OXYTOCIN ON NEUROCHEMICAL METABOLITES IN PSYCHOSIS RISK. (9th April 2019) - Davies, Cathy; Rutigliano, Grazia; Micheli, Andrea De; Stone, James M; Ramella-Cravaro, Valentina; Provenzani, Umberto; Cappucciati, Marco; McGuire, Philip; Fusar-Poli, Paolo
Abstract: Background: Accumulating research suggests that altered levels of neurochemical metabolites -such as glutamate- play a role in psychosis pathophysiology, are present prior to onset in people at Clinical High Risk (CHR-P) and predict clinical outcomes. Oxytocin, a neuropeptide with prosocial and anxiolytic properties, modulates glutamate neurotransmission in animals but its neurochemical effects in CHR-P individuals remain unknown. The present study examined the effects of intranasal oxytocin on glutamate and glutamate+glutamine (primary hypothesis) and other neurochemical metabolites (secondary hypothesis) in CHR-P individuals. Methods: In a double-blind, placebo-controlled, crossover design, 30 CHR-P males underwent two MRI scans at 3 Tesla, once after 40IU intranasal oxytocin and once after matched placebo (one-week wash-out). Proton magnetic resonance spectroscopy (1H-MRS) was used to measure the effects of oxytocin on glutamate, glutamate+glutamine and other metabolite levels (choline, N-acetylaspartate, myo-inositol) scaled to creatine in the hippocampus, anterior cingulate cortex and thalamus. Results: Data analysis is currently ongoing, and the results will be presented at the conference. Discussion: These results will provide the first neurophysiological evidence for the potential effects of oxytocin on neurochemical metabolites in CHR-P individuals. Given the current lack of evidence for effective treatments in this patient group, continued efforts to find novel molecules with a relevant profile of effects remains a priority.